Airflow temperature and humidity patterns in a screenhouse with a flat insect-proof screen roof and impermeable sloping walls – Computational fluid dynamics (CFD) results. (February 2022) - Teitel, Meir; Ozer, Shay; Mendelovich, Vered
Abstract : Insect-proof screenhouses are commonly used to grow plants in warm climates. However, there is relatively little literature on their microclimate compared to greenhouses. This study presents computational fluid dynamics (CFD) results of airflow, temperature, and humidity ratio patterns in a screenhouse with a roof consisting of a large flat insect-proof screen and impermeable walls. First, vertical profiles of velocity, temperature, and humidity at the center of the screenhouse were obtained by 2D steady-state CFD simulations and validated by experimental results. Root mean square error (RMSE) values were used to measure the differences between the two. The lowest RMSE values among simulations with different turbulence models were 0.49 K, 1.26 g kg −1, and 0.05 m s −1 (with the RNG turbulence model) for temperature, humidity ratio, and air velocity, respectively. The main deviation of the CFD results from the experimental results was observed with the air velocity in the upper region of the screenhouse. Inflow and outflow in the leeward and windward parts of the flat roof were observed, respectively. This resulted in large-scale airflow within the screenhouse opposite the outside wind direction at the canopy level. The results suggested that the leeward section of the screenhouse is warmer than the windward one and has a lower humidity ratio. Large-scale rotating airflow formed in the center of the screenhouse, close to the roof, a large area with a humidity ratio similar to ambient conditions. Highlights: CFD simulations are used to determine airflow, temperature and humidity patterns. CFD and experimental results were in agreement except of velocity near screenhouse top. Airflow within the canopy of an insect-proof screenhouse was opposite to wind direction. From windward to leeward ends the temperature increased and humidity decreased.